1992
DOI: 10.1038/bjc.1992.102
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of photodynamic therapy with 99technetium HMPAO scintigraphy

Abstract: Summary The effect of photodynamic therapy (PDT) on tumour perfusion in both anaplastic (R3327-AT) and well differentiated (R3327-H) Dunning prostatic tumours was studied using the radiopharmaceutical 99Technetium hexamethylpropyleneamine oxime (99"Tc-HMPAO). Tumours in the left flanks of rats (Copenhage x Fischer, F1 hybrids) were treated with interstitial PDT when their volumes reached 2-3 cm3. Qualitative and quantitative data from pre-and post-PDT scintigraphy revealed a light-dose-dependent shut-down of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…These findings are comparable to our data obtained with 5 mg kg-I, because PI1 is at least two times more active than HPD (25). Using scintigraphy with 99mTc-HMPA0, Moore et al (13) observed a light-dose-dependent shut-down in tumor perfusion following PII-PDT in rats (tumor size: 2-3 cm3). Quantitative comparison of this study with our data is difficult because most of their TVP values were determined following PDT at 2 h after drug administration, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are comparable to our data obtained with 5 mg kg-I, because PI1 is at least two times more active than HPD (25). Using scintigraphy with 99mTc-HMPA0, Moore et al (13) observed a light-dose-dependent shut-down in tumor perfusion following PII-PDT in rats (tumor size: 2-3 cm3). Quantitative comparison of this study with our data is difficult because most of their TVP values were determined following PDT at 2 h after drug administration, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…This constraint together with the necessity to use arterial cannulation to avoid the peripheral circulation and the immediate trapping of the microspheres by the lungs, render this method difficult to apply in mice. As it was demonstrated with 99mTc-HMPA0 (13,14), 9h"T~-MIBI could be useful for the noninvasive monitoring of TVP by scintigraphy, at least in the case where the tumor size is higher than the resolution of the y-camera, which was not the case in our tumor model. These two perfusion agents have recently been compared in tumor-bearing rabbits for their potential use as tumor-imaging agents (26).…”
Section: Discussionmentioning
confidence: 69%
“…The dual hypoxic marker technique was further investigated with Dunning R3327-AT and R3327-H tumours growing in Fischer x Copenhagen rats. The radiosensitivity, perfusion status and spontaneous and photodynamic therapy-induced hypoxia in these tumour models have been reported previously (Thorndyke et al, 1985;Chapman et al, 1991;Moore et al, 1992Moore et al, , 1993. The average radiobiological HF of R3327-AT tumours is -15%, whereas the R3327-H tumour is well perfused with no measurable HF by the radiobiological or hypoxic marker techniques (Thorndyke et al, 1985).…”
Section: Resultssupporting
confidence: 71%
“…Tumour growth was monitored twice weekly until tumours reached volumes of 5-10 cm3 as determined from three mutually perpendicular measurements of tumour diameter made with callipers (Thorndyke et al, 1985). Previous studies (Thorndyke et al, 1985;Chapman et al, 1991;Moore et al, 1992Moore et al, , 1993 had shown R3327-AT tumours to exhibit both inter-and intratumour heterogeneity of blood flow and perfusion with an average radiobiological HF of -15%. The well-differentiated R3327-H tumour showed no evidence of significant HF by radiobiological and hypoxic marker assays (Thorndyke et al, 1985).…”
Section: Materials and Methods Hypoxic Markersmentioning
confidence: 97%
“…administration of 15 mg/kg Photofrii. 18 The tumor volumes treated in the first study16 were between 0.5-0.8 cm3 and those treated in the other study'8 were 2-3 cm3. Tumor response observed in these studies was by tumor perfusion shutdown and secondary ischemic tumor cell death.…”
Section: Discussionmentioning
confidence: 99%